PEMETAAN MASALAH UNTUK PENGEMBANGAN MODUL KEWIRAUSAHAAN DI MASA PANDEMI COVID 19 - Hairunisya, Nanis (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
Problem analysis for the development of the entrepreneurship module during the covid 19 pandemic. This study aims to map learning problems to improve students' higher order thinking skills (HOTS) in the context of developing an entrepreneurship module during the covid 19 pandemic. The analysis is carried out with the stages of front end analysis, learner analysis, task analysis and concept analysis. Qualitative approach case study is used as a research method. The data were analyzed by coding, categorizing, eliminating, combining and dividing the data to see the relationship between the existing themes. The results of mapping problems in the classroom are internet stability is not good, often students do not focus on the material provided, limited expressing opinions, always passive when given the opportunity to ask questions, students' ability in making business plans is still low, especially in grammar, students' unpreparedness to learn independent. Results Identification of students' abilities in achieving learning objectives with indicators of student abilities, basic competencies, learning objectives; and indicators & entrepreneurship studies have a value of 61%. This indicates that efforts are needed in learning so that student competence increases as expected. The implication of this research is that the layout of the entrepreneurship module has been made using replication and simulation methods. This is in line with the policy of the Ministry of Education and Culture, namely the Merdeka Campus, Merdeka Learning, which encourages lecturers to improve their competence, especially in collaborating with students and the community in producing products that are needed by the community.